2020
DOI: 10.1101/2020.06.03.131359
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decomposition of reinforcement learning deficits in gambling disorder via drift diffusion modeling and functional magnetic resonance imaging

Abstract: Gambling disorder is associated with deficits in classical feedback-based learning tasks, but the computational mechanisms underlying such learning impairments are still poorly understood. Here, we examined this question using a combination of computational modeling and functional resonance imaging (fMRI) in gambling disorder participants (n=23) and matched controls (n=19). Participants performed a simple reinforcement learning task with two pairs of stimuli (80% vs. 20% reinforcement rates per pair). As predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 86 publications
(158 reference statements)
6
16
0
Order By: Relevance
“…Model comparison revealed that the DDM S had the lowest DIC in all conditions (Table 4) replicating previous work [45,46,48] . Consequently, further analyses of session effects and reliability focused on this model.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Model comparison revealed that the DDM S had the lowest DIC in all conditions (Table 4) replicating previous work [45,46,48] . Consequently, further analyses of session effects and reliability focused on this model.…”
Section: Resultssupporting
confidence: 87%
“…This was observed for model-free measures (AUC), as well as the log(k) parameter of the hyperbolic discounting model with the softmax choice rule and the drift diffusion model with non-linear drift rate scaling (DDM S ). Model comparison revealed that the DDM S accounted for the data best, confirming previous findings [43,45,46,48] . Although generally, discount rates assessed in the three sessions were of similar magnitude, in the DDM S there was moderate evidence for reduced discounting (i.e., smaller values of log(k) ) in the VR neutral session.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations